2011
DOI: 10.1097/tp.0b013e31821cdea5
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Increases Survival and Attenuates Fulminant Hepatic Failure Injury Induced by d-Galactosamine/Lipopolysaccharide in Mice

Abstract: The administration of rhEPO brought about increased survival and attenuation of the hepatic injury. This was associated with decreased hepatic NF-κB and JNK activation and thus TNF-α and IL-1β levels. These findings have important implications for the potential use of rhEPO in FHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…37 In the present study, 5′-AMP could not inhibit LPS-induced nuclear translocation of NF- κ B p65, but suppressed transactivation activity of NF- κ B. It is known that histone methylation could modulate NF- κ B downstream genes.…”
Section: Discussioncontrasting
confidence: 52%
“…37 In the present study, 5′-AMP could not inhibit LPS-induced nuclear translocation of NF- κ B p65, but suppressed transactivation activity of NF- κ B. It is known that histone methylation could modulate NF- κ B downstream genes.…”
Section: Discussioncontrasting
confidence: 52%
“…We and others found that ischemia alone can activate this pathway [6,50]. Moreover, the role of JNK in myocardial ischemia/reperfusion (I/R) remains controversial, since equally robust studies have reported dichotomous results suggesting both cardioprotective [51][52][53] and detrimental effects [6,49,54]. In contrast to our previous report, we have found a significant reduction in the expression of phospho-cJun in wild type (WT) mice pretreated with UTP compared to MI alone (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The toll like receptor 4 (TLR4) recognizes endogenous free fat acid and exogenous pathogens [20], [21] and engagement of TLR4 activates the nuclear factor κB (NF-κB) [22] and mitogen-activated protein kinase (MAPK) subfamily members [23], including the extracellular-signal-regulated kinase (ERK), c-Jun N-terminal kinases (JNK) and p38 MAPK, as well ascytokines [24], and stimulates the production of inflammatory cytokines, such as tumor necrosis factor (TNF)-α and interleukin (IL)-6, contributing to glucose intolerance and insulin resistance. Given that EPO treatment inhibits the NF-κB, ERK and JNK activation, and TNF-α and IL-6 production in animal models of hepatic injury [25][28], we hypothesize that EPO may also inhibit the HFD-induced chronic inflammation, contributing to the improvement of glucose intolerance and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%